Capital Flight and Economic Growth in Nigeria: A New Evidence from ARDL Approach - Orji, Anthony; Ogbuabor, Jonathan E.; Kama, Kenneth; Anthony-Orji, Onyinye I. (Asian Development Policy Review, 2020)
The issue of capital flight has been a recurrent topic of discussion among researchers especially in Africa. The cause, magnitude and consequences of this undesirable outflow of domestic capital have been a persistent concern among scholars. Nigeria among other African countries has been a victim of massive capital outflow to other developed nations. Thus, this study investigated the impact of capital flight on economic growth in Nigeria. In carrying out the analysis, data from CBN statistical bulletin was used for the period 1981 to 2017. The Autoregressive Distributed Lag (ARDL) bounds test approach was adopted for the study. The study showed that capital flight significantly decreases economic growth in both short run and long run. Other variables found to have significant effect on economic growth include money supply, credit to private sector and domestic investment. The study therefore recommended proactive policy measures that will curtail capital flight and make the economy competitive and attractive for domestic investment that enhances economic growth. Expansionary monetary policy should also be adopted to improve money supply whenever the policy environment is ripe for such.